2010
DOI: 10.1038/onc.2009.513
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl regulates estrogen receptor α transcription activity through its stabilization by phosphorylation

Abstract: Estrogen receptors are members of the steroid hormone superfamily of nuclear receptors that act as ligandactivated transcription factors. Similar to other steroid hormone receptors, estrogen receptor a (ERa) is a substrate for protein kinases, and phosphorylation has profound effects on the function of this receptor. In this study, we show that ERa associates with c-Abl nonreceptor tyrosine kinase. The direct interaction is mediated by two PXXP motifs of ERa and the c-Abl SH3 domain. Mutational analysis and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…However, we cannot rule out whether Y537-independent mechanisms may also be involved in the PTPH1-induced sensitization. One recent study reported that ER is also phosphorylated at Y52 and/or Y219 by c-Abl, which is involved in breast cancer invasion and growth (34). Moreover, studies with a 6-amino acid peptide that mimics the sequence around the phosphotyrosine residue 537 showed that it disrupted the Src-ER interaction and blocked breast cancer growth in vitro and in mice (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot rule out whether Y537-independent mechanisms may also be involved in the PTPH1-induced sensitization. One recent study reported that ER is also phosphorylated at Y52 and/or Y219 by c-Abl, which is involved in breast cancer invasion and growth (34). Moreover, studies with a 6-amino acid peptide that mimics the sequence around the phosphotyrosine residue 537 showed that it disrupted the Src-ER interaction and blocked breast cancer growth in vitro and in mice (35).…”
Section: Discussionmentioning
confidence: 99%
“…The reporter constructs ERE-Luc, catD-Luc, and pS2-Luc and the expression vectors for ERα, Flag-tagged ERα, and HA-tagged ERα have been described previously (46). Other mammalian expression vectors encoding Flag-, Myc-, or HA-fusion proteins tagged at the amino terminus were constructed by inserting PCR-amplified fragments into pcDNA3 (Invitrogen) or pIRESpuro2 (Clontech).…”
Section: Methodsmentioning
confidence: 99%
“…Cell extracts were prepared, immunoprecipitated, and analyzed as previously described (46). An aliquot of the total lysate [5% (vol/vol)] was included as a control for the interaction assay.…”
Section: Methodsmentioning
confidence: 99%
“…The estrogen-responsive reporter construct ERE-Luc and eukaryotic expression vectors for FLAG-tagged ERα and ERβ have been described previously (57)(58)(59). Other mammalian expression vectors encoding FLAG-, MYC-, or HA-fusion proteins tagged at the amino terminus were constructed by inserting PCR-amplified fragments into pcDNA3 (Invitrogen) or pIRESpuro2 (Clontech).…”
Section: Methodsmentioning
confidence: 99%